EFL Students' Perception on Strengths and Weaknesses of Group Working in Project-Based Learning - Sri Munianti; Suhartini Syukri (AL LUGHAWIYAAT, 2021)
This study investigates the EFL students' perception on Strengths and weaknesses of group working in project-based learning. This implements qualitative research of study. Data were collected using reflections, which were distributed to 15 students of the fifth semester at the English Education Study Program in higher education at Kendari as participant. The finding showed that there were strengthen and weaknesses in implementing group work on PBL. Some strengthen on group work do PBL are brainstorming ideas, providing easier learning, and understanding material, practicing cooperation skills, sharing the task inside team and developing responsibilities. Meanwhile, for the weaknesses of group work on PBL namely the students’ feel their group member was incohesive team these included of lack unity and think of themselves, difficulties to set time, uneven assigment, and misunderstanding in the discussion group. This study implies the lecturer or prospective teacher should have some considerations when they want to use group work activities in the class.